2017
DOI: 10.1017/s0024282917000287
|View full text |Cite
|
Sign up to set email alerts
|

The genus Xenolecia (Lecideaceae s. lat., Lecanoromycetidae inc. sed.), including a second species in the genus from Campbell Island, New Zealand

Abstract: The new species Xenolecia cataractarum Fryday is described from Campbell Island. It differs from X. spadicomma, the only other species of the genus, in having much smaller apothecia and ascospores, an olivaceously pigmented epihymenium (brown in X. spadicomma), and a thallus with a non-amyloid medulla and norstictic acid (amyloid medulla and confluentic acid in X. spadicomma). Xenolecia spadicomma is reported here from several localities on the Falkland Islands and three from the Región de Los Lagos, Chile, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…This is possibly due to differing degrees of maturity of the asci, with immature asci having only the external cap that later develops the internal horizontal sheets, with the tube-like structure developing only in fully mature asci. A similar process has been documented in the asci of Xenolecia Hertel, with immature asci having an internal cap (Lecidea-type) that develops a tube structure (Porpidia-type) when mature (Fryday & Thüs 2017).…”
Section: (Figs 2-4)supporting
confidence: 60%
“…This is possibly due to differing degrees of maturity of the asci, with immature asci having only the external cap that later develops the internal horizontal sheets, with the tube-like structure developing only in fully mature asci. A similar process has been documented in the asci of Xenolecia Hertel, with immature asci having an internal cap (Lecidea-type) that develops a tube structure (Porpidia-type) when mature (Fryday & Thüs 2017).…”
Section: (Figs 2-4)supporting
confidence: 60%
“…The genus Xenolecia is characterized by having Porpidia-type asci, innate (aspicilioid) apothecia with a brown disc and abundant pycnidia containing filiform conidia (Hertel 1984). All three described species occur in damp habitats subject to periodic inundationmost often on rocks in or beside streams (Fryday & Thüs 2017). Fryday et al (2021) suggested that L. masafuerensis was probably a synonym of X. spadicomma, but closer examination has shown a number of differences: X. masafuerensis has smaller apothecia (0.5-2.2 mm diam.…”
Section: Taxonomymentioning
confidence: 99%
“…Cunningham from Isla Wellington in southern Chile in 1868 (Crombie 1876). Fryday & Thüs (2017) reported additional records of this species from Los Largos Region, Chile and from several localities on the Falkland Islands, and also reported a second species in the genus, X. cataractarum Fryday, from Campbell Island New Zealand. Here, a third species is added to the genus from the Juan Fernandez archipelago, Chile.…”
Section: Introductionmentioning
confidence: 96%